MEMBANGUN KELUARGA SAKINAH - Sofyan Basir (240-540X)
Realizing the family of Sakinah Mawaddah and Warohmah is the desire of every human being. How happy we are to have a family filled with mutual love, love, protect and respect. But apparently realizing a family like that is not the work of turning the palm of the hand. It takes great effort and support from all parties in the family both father, mother and child. The biggest responsibility is the father who acts as the head of the family. Father's role is very vital which acts as a captain who will move where the ship will sail and dock. Mothers also play a small role in building the character and character of children and managing family finances. However, it is not uncommon for them to find a dead end, both with material kissing and the needy.